Experimental and numerical investigation of a tube-in-tank latent thermal energy storage unit using composite PCM. (15th March 2017) - Meng, Z.N.; Zhang, P.
Highlights: A tube-in-tank latent thermal energy storage (LTES) unit using composite PCM is built. Thermal performances of the LTES unit are experimentally and numerically studied. Thermal performances of the LTES unit under different operation conditions are comparatively studied. A 3D numerical model is established to study the heat transfer mechanisms of the LTES unit. Abstract: Paraffin is a commonly used phase change material (PCM) which has been frequently applied for thermal energy storage. A tube-in-tank latent thermal energy storage (LTES) unit using paraffin as PCM is built in the present study, which can be used in many applications. In order to enhance the thermal performance of the LTES unit, the composite PCM is fabricated by embedding copper foam into pure paraffin. The performances of the LTES unit with the composite PCM during the heat charging and discharging processes are investigated experimentally, and a series of experiments are carried out under different inlet temperatures and inlet flow velocities of the heat transfer fluid (HTF). The temperature evolutions of the LTES unit are obtained during the experiments, and the time-durations, mean powers and energy efficiencies are estimated to evaluate the performance of the LTES unit. Meanwhile, a three-dimensional (3D) mathematical model based on enthalpy-porosity and melting/solidification models is established to investigate the heat transfer mechanisms of the LTES unit and the detailed heat transfer characteristics of the LTES unit are obtained. It can be concluded that the LTES unit with the composite PCM shows good heat transfer performance, and larger inlet flow velocity of the HTF and larger temperature difference between the HTF and PCM can enhance the heat transfer and benefit the thermal energy utilization. Furthermore, a LTES system with larger thermal energy storage capacity can be easily assembled by several such LTES units, which can meet versatile demands in applications.